PENGEMBANGAN MODEL HEWAN DISMENOREA DAN UJI AKTIVITAS EKSTRAK ETANOL DAUN BARU CINA (ARTEMISIA VULGARIS L.) PADA MENCIT MODEL DISMENOREA - Fadilla Dzulfia, Chitra
Primary dysmenorrhoea is a widely common complaint among young women during menstruation, and a painful menstrual cramps without any evident with gynecological abnormalities. Artemisia vulgaris L. is traditionaly known to have efficacy in dealing with various problems of the menstrual cycle. This study aims to test the activity of anti¬dysmenorrhea from ethanol extract Artemisia vulgaris L. leaves using dysmenorrhea animal models. The mice were given with estradiol 0.01 g/kg bw by subcutaneous injection for 7-15 days. On the last day, the mice were injected intraperitoneally with oxytocin a dose of 2 IU/kg bw and 3 IU/kg bw. Number of writhing was recorded. The female mice were divided into five groups, normal group, control, group with ethanol extract A. vulgaris leaves 250mg/kg bw, group with ethanol extract A. vulgaris leaves 500 mg/kg bw , Kiranti 15 ml/kg bw and ibuprofen 52 mg/kg bw. The optimum dysmenorrhea model in mice was established by estradiol 0.01 g/kg bw given for 15 days and on the 15th day the mice were injected intraperitoneally with oxytocin in dosage 3 lU/kg bw. Group treated with ethanol extract of A. vulgaris leaves 250 mg/kg bw and dose 500mg/kg bw present significant difference decreased number of writhing (p <0.05) compared with the control group. Groups of animals were given ethanol extract A. vulgaris leaves 500 mg/kg had increased time writhing statistically significantly different (p <0.05) compared to the control group. It has been established dysmenorrhea animal models by administration of estradiol 0.01 g/kg bw for 15 days and induced with oxytocin dose of 3 IU / kg bw. Ethanol extract of A. vulgaris leaves dose 500 mg/kg and dose 250 mg/kg bw proven to give the of anti-dysmenorrhea effect. The increased of anti-dysmenorrhoea effect was shown proportionaly to the increased of dose of extract.